2020
DOI: 10.1111/1462-2920.15317
|View full text |Cite
|
Sign up to set email alerts
|

Communal living: glycan utilization by the human gut microbiota

Abstract: Summary Our lower gastrointestinal tract plays host to a vast consortium of microbes, known as the human gut microbiota (HGM). The HGM thrives on a complex and diverse range of glycan structures from both dietary and host sources, the breakdown of which requires the concerted action of cohorts of carbohydrate‐active enzymes (CAZymes), carbohydrate‐binding proteins, and transporters. The glycan utilization profile of individual taxa, whether ‘specialist’ or ‘generalist’, is dictated by the number and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 246 publications
(448 reference statements)
0
55
0
Order By: Relevance
“…To a lesser extent, the Mesolithic foragers from the Danube Gorges and Italy showed the enrichment of the utilization systems for glycans and polysaccharides pathway, detected also in the chimpanzees. This pathway is associated with carbohydrate‐active enzymes that enable the breakdown of dietary glycans, including, among others, plant storage and cell wall polysaccharides ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…To a lesser extent, the Mesolithic foragers from the Danube Gorges and Italy showed the enrichment of the utilization systems for glycans and polysaccharides pathway, detected also in the chimpanzees. This pathway is associated with carbohydrate‐active enzymes that enable the breakdown of dietary glycans, including, among others, plant storage and cell wall polysaccharides ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteroidaceae, bifidobacteria have maintained symbiosis with their hosts during hominid evolution over 15 million years [9]. The central role of glycan catabolism in this successful adaptation [10,11] is consistent with the abundance of Bacteroides and Bifidobacterium [12]. Polysaccharide utilization loci (PULs) that encode TonB-dependent oligosaccharide transporters, transcriptional regulators and one or several outer-membrane attached and periplasmic carbohydrate-active enzymes (CAZymes) that target a specific glycan have been proposed to promote human colonisation by Bacteroides [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that Bacteroides species with overlapping substrate spectra limit competition with each other by prioritising different carbohydrates when grown together on a mix of substrates (30,31) . The initial polysaccharide degradation in Bacteroidetes takes place at the cell surface and oligosaccharides are imported across the outer membrane into the periplasmic space for further degradation and transport into the cytoplasm (6) . Species within the other dominant phylum, the Firmicutes, contain fewer CAZymes on average than Bacteroidetes species (27) and often have smaller genomes overall.…”
Section: Genetics and Physiology Of Fibre Breakdown Strategies In Gut Microbesmentioning
confidence: 99%
“…Species within the other dominant phylum, the Firmicutes, contain fewer CAZymes on average than Bacteroidetes species (27) and often have smaller genomes overall. However, there is also large variation between the many different species (3,6) . For example, a study of genomes from eleven strains belonging to five Firmicutes species within the Roseburia spp./Eubacterium rectale group of the Lachnospiraceae family showed that most strains harboured between 56 and 86 glycoside hydrolase genes, whereas the three Roseburia intestinalis strains contained between 102 and 146 (32) .…”
Section: Genetics and Physiology Of Fibre Breakdown Strategies In Gut Microbesmentioning
confidence: 99%